Automating the measurement of critical thinking in discussion forums : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Ph.D.) in Information Systems at Massey University, Palmerston North, New Zealand - Corich, Stephen Paul (Massey University, 2011)
Critical thinking is seen as an essential skill for survival in the 21st century and those involved in education agree that encouraging students to think critically is an essential requirement of the educational system. There is considerable debate among educationalists concerning the most effective way to encourage the development of critical thinking skills and little agreement on the best way to measure evidence of critical thinking. This study examines what is meant by the term critical thinking and investigates some of the tools that have been used to measure evidence of critical thinking. The study concentrates on the measurement of critical thinking among discussion forum participants and describes the development and testing of a tool designed to automate the process of measuring critical thinking. Since the study involved the design, development and testing of a computerised tool, an action research approach was adopted. Action research gained popularity among information systems developers around the mid 1990s. It is seen as a methodology that encourages the generation of scientific knowledge by allowing the researcher to modify intentionally a real setting and carefully evaluate the results. The study describes the development of an automated text classification system that uses content analysis to classify discussion forum transcripts using critical thinking models developed by Garrison, Anderson, & Archer (2000), Henri (1992) and Perkins & Murphy (2006). The findings from the study suggest that automated tools have the potential to assist in the measurement of critical thinking abilities and are worthy of further investigation.
Keywords: Critical thinking; Measurement; Electronic discussion groups; Content analysis (Communication); Data processing